2017
DOI: 10.1063/1.5003521
|View full text |Cite
|
Sign up to set email alerts
|

Phase identification and morphology study of hematite (Fe2O3) with sintering time varitions

Abstract: Abstract. Iron oxide has been the interest of many studies due to its applications in various scientific and industrial fields including in environment, corrosion, soil science, and exhaust emissions. Iron oxide (Fe2O3) has potential applications in catalytic reactions in electronic devices such as semiconductors, paint formulations, and lithium rechargeable batteries. Fe2O3 can be synthesized through the process of stirring, decomposition of organic iron, sol-gel, combustion, and evaporating solvents. Most of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…This may provide iron oxides in the Ni− Fe/MS catalyst, thus increasing acidic sites to promote the deoxygenation ability and enable better selectivity. These results also agree with those presented by Zhai et al 14 So far, several researchers have reported the effect of the Ni−Fe ratio on various supports, such as activated carbon, 14 mesoporous carbon spheres, 41 and CeO 2 −Al 2 O 3 . 48 The results revealed that Ni−Fe in a 1:1 ratio exhibited better performance in lignin depolymerization than the monometallic catalyst.…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…This may provide iron oxides in the Ni− Fe/MS catalyst, thus increasing acidic sites to promote the deoxygenation ability and enable better selectivity. These results also agree with those presented by Zhai et al 14 So far, several researchers have reported the effect of the Ni−Fe ratio on various supports, such as activated carbon, 14 mesoporous carbon spheres, 41 and CeO 2 −Al 2 O 3 . 48 The results revealed that Ni−Fe in a 1:1 ratio exhibited better performance in lignin depolymerization than the monometallic catalyst.…”
Section: Methodssupporting
confidence: 92%
“…00-002-0546). On the other hand, the main diffraction peaks of 20Fe/MS at 2θ 43.50° for Fe and 2θ 33.35, 55.90, and 62.30°, additionally observed, confirmed the formation of Fe 2 O 3 . 20Ni/MS also showed diffraction peaks at 2θ 43.90, and 76.80°, indicating the existence of 111 and 220 planes of Ni, respectively .…”
Section: Resultsmentioning
confidence: 72%
“…8 shows the XRD analysis of the calcined samples of As(III) and As(V). The XRD pattern confirms the formation of ferric oxide in both the precipitates 71. The peak positions obtained are 24.12 (012), 33.16 (104), 35.64 (110), 40.88 (113), 49.44 (024), 54.06 (116), 57.56 (018), 62.42 (214), and 63.98 (300).…”
Section: Resultssupporting
confidence: 58%
“…The corresponding 2θ peaks located at ∼24°, 33°, 35°, 41°, 50°, 54°, 58°, 62°, and 64° represent the crystal planes of (012), (104), (110), (113), (024), (116), (018), (214), and (300), respectively. 24,25 No secondary phases were observed, indicating the high purity of the synthesized materials. As depicted in Fig.…”
Section: Resultsmentioning
confidence: 97%